PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS VISUAL BASIC.NET DAN MS. ACCES PADA TOKO 99 DI KARAWANG - Adithya Yudi Darmawan; Adhy Rifqi Wirabuana (POLITEKNIK PIKSI GANESHA, 2021)
The provision of data processing, a grocery store still employs the conventional recording method upon which the entire data is written in a book or archive. A computerized system for handling data processing has not been provided, causing the needed information and report creation to be late, so as to the lack of a integrated document between each transaction and the purchase part and the storage and the problem in which excess and shortage of supplies impede the production process. The design of this system using Microsoft visual basic 2010 was selected to be the software of supply information systems using the 2010 Microsoft acces database. It is hoped that this system makes it easier for the wearer to control the supply of the goods, to calculate the inventory in the storehouses correctly, and to produce precise and accurate reports. Keywords: inventory, storage, administration